2020
DOI: 10.1029/2020gl088447
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Strength Variations Inferred From Earthquake Stress Drop at Axial Seamount Surrounding the 2015 Eruption

Abstract: Variations in stress drops of earthquakes associated with the April and May 2015 eruption of Axial Seamount, on the Juan de Fuca Ridge, suggest a reduction in crustal strength as a result of the eruption. Seismicity during the inflation and deflation periods was well recorded by ocean bottom seismometers located within and along the caldera. We use these nearby recordings and an empirical Green's function spectral ratio method to obtain corner frequencies for stress drops of earthquakes on caldera ring faults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Ruhl et al [72] suggested that temporal variations in stress drop during a swarm sequence may reflect long-term spatial variations, combined with temporal variation in the spatial distribution of the earthquakes. Yoshida et al [178] reported temporal variation in stress drop associated with fluid migration and seismicity rate in a productive swarm in NE Japan, Goertz-Allmann et al [179] and Kwiatek et al [132] reported a decrease in stress drop associated with higher pore fluid pressure during geothermal injection in Switzerland and El Salvador, respecrively and Moyer et al [180] reported a systematic change in stress drop for earthquakes following an eruption at the Axial seamount. To varying degree, all these observations are subject to possible artefacts from temporal variation in the surrounding medium (e.g.…”
Section: Discussion and Assessment Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruhl et al [72] suggested that temporal variations in stress drop during a swarm sequence may reflect long-term spatial variations, combined with temporal variation in the spatial distribution of the earthquakes. Yoshida et al [178] reported temporal variation in stress drop associated with fluid migration and seismicity rate in a productive swarm in NE Japan, Goertz-Allmann et al [179] and Kwiatek et al [132] reported a decrease in stress drop associated with higher pore fluid pressure during geothermal injection in Switzerland and El Salvador, respecrively and Moyer et al [180] reported a systematic change in stress drop for earthquakes following an eruption at the Axial seamount. To varying degree, all these observations are subject to possible artefacts from temporal variation in the surrounding medium (e.g.…”
Section: Discussion and Assessment Of Measurementsmentioning
confidence: 99%
“…[179] and Kwiatek et al [132] reported a decrease in stress drop associated with higher pore fluid pressure during geothermal injection in Switzerland and El Salvador, respecrively and Moyer et al . [180] reported a systematic change in stress drop for earthquakes following an eruption at the Axial seamount. To varying degree, all these observations are subject to possible artefacts from temporal variation in the surrounding medium (e.g.…”
Section: Discussion and Assessment Of Measurementsmentioning
confidence: 99%
“…Some studies reported complete or near‐complete stress drop during tectonic earthquakes (Hasegawa et al., 2011; Ross et al., 2017), while the stress drop ratio can be partial and vary from earthquake to earthquake (Hardebeck & Okada, 2018). For intra‐caldera earthquakes, several recent studies estimated stress drop during caldera collapses (Moyer et al., 2020; T. A. Wang et al., 2022), but our knowledge on the stress drop ratio in calderas is poor and the ratio may vary from caldera to caldera.…”
Section: Discussionmentioning
confidence: 99%
“…We then calculate average stress drop values (trueσ $\overline{{\increment}\sigma }$ Forearc ) at 10‐km depth intervals with 50% overlap (Text S3 and S4 and Figures S8 and S9 in Supporting Information ). The averaged values better reflect bulk stress conditions in the forearc and are better suited for comparison with modeled stresses (Moyer et al., 2020).…”
Section: Comparison Of Model Stresses With Static Stress Drop Of Fore...mentioning
confidence: 99%
“…We then calculate average stress drop values ( 𝐴𝐴 ∆𝜎𝜎 Forearc ) at 10-km depth intervals with 50% overlap (Text S3 and S4 and Figures S8 and S9 in Supporting Information S1). The averaged values better reflect bulk stress conditions in the forearc and are better suited for comparison with modeled stresses (Moyer et al, 2020).…”
Section: Comparison Of Model Stresses With Static Stress Drop Of Fore...mentioning
confidence: 99%